A Generalized (G'/G)-expansion Method to Find the Traveling Wave Solutions of Nonlinear Evolution Equations (Journal of Partial Differential Equations, 2018)
In this article, we construct the exact traveling wave solutions for nonlinear evolution equations in the mathematical physics via the modified Kawahara equation, the nonlinear coupled KdV equations and the classical Boussinesq equations, by using a generalized (G'/G)-expansion method, where G satisfies the Jacobi elliptic equation. Many exact solutions in terms of Jacobi elliptic functions are obtained.
Keywords: A generalized (G'⁄ G)-expansion method; traveling wave solutions; the modified Kawahara equation; the coupled KdV equations; the classical Boussinesq equations; the Jacobi elliptic functions